Ritual Ziarah Masyarakat Kapota di Makam (Koburu) La Bapa Kapota - Arisludin Arisludin; Wa Ode Winesty Sofyani (JURNAL KABANTI: Kerabat Antropologi, 2022)
This study aims to determine the Pilgrimage Ritual of the Kapota Community in KoburuLa Ayah: Study in Kapota Village, South Wangi-wangi District, Wakatobi Regency. The theory used refers to the theory of Victor Turner. The author uses a qualitative descriptive method by carrying out several stages namely, observation, regular interviews, in-depth interviews, and involved observations which then the data obtained are analyzed using the ethnographic method.The results showed that the Kapota community believed and used to eat La Ayah at the Togo Molengo Fort as a means for mystical rituals such as traditional and religious ceremonies, such as making pilgrimages or vows, praying for safety and healing from all diseases, by means of intermediary blessings and the holiness of La Father or Mr. Barakati who is considered a sacred person and an ancestor. Through this intermediary Mr. Barakati, it is believed that he is able to eliminate and restore sick people.